2004
DOI: 10.1590/s0103-50532004000300007
|View full text |Cite
|
Sign up to set email alerts
|

Organic/inorganic hybrid materials formed from TiO2 nanoparticles and polyaniline

Abstract: Este artigo descreve a síntese e caracterização de diferentes híbridos orgânico/inorgânicos formados entre a polianilina e o óxido de titânio. O método de preparação é baseado no processo sol-gel, partindo do isopropóxido de titânio como precursor. Duas rotas sintéticas visando a obtenção dos híbridos foram utilizadas, baseadas na mistura da anilina no meio reacional antes ou após a formação do óxido. Diferentes quantidades de anilina foram utilizadas visando compreender este efeito nas características do mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 44 publications
0
27
0
3
Order By: Relevance
“…For this particular specimen an average thickness of 33 lm corresponded to a redox charge of 350 mC cm -2 and a very high surface roughness (morphology features with height between 25 and 50 lm) was observed. On the other hand SEM on TiO 2 -PANI-coated graphite substrates with composite layers produced through a few (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) potentiodynamic scans showed incomplete coverage of the underlying substrate by the polymer layer. For this reason in the text we have always specified the redox charge of the deposited composites instead of the polymer layer thickness.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…For this particular specimen an average thickness of 33 lm corresponded to a redox charge of 350 mC cm -2 and a very high surface roughness (morphology features with height between 25 and 50 lm) was observed. On the other hand SEM on TiO 2 -PANI-coated graphite substrates with composite layers produced through a few (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) potentiodynamic scans showed incomplete coverage of the underlying substrate by the polymer layer. For this reason in the text we have always specified the redox charge of the deposited composites instead of the polymer layer thickness.…”
Section: Experimental Partmentioning
confidence: 99%
“…Various attempts have been made to incorporate TiO 2 nanoparticles in conducting polymer materials with the aim of obtaining composites with high conductivity [1], high piezoresistivity [2], high photoconductivity [3], improved battery storage characteristics [4] and corrosion protection properties [5] or for light image formation [6]. Most of the work in the field [1][2][3][7][8][9][10][11] was performed by using chemical approaches for the synthesis of composite polyaniline (PANI) and polythiophene-based materials. Electrochemical synthesis has been used in a few studies, i.e., in the case of TiO 2 /PANI [1,6,12] and TiO 2 /polypyrrole [5,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…O espectro UV-Vis do sal esmeraldina apresenta três bandas características: duas bandas em aproximadamente ~ 320 -380 nm e ~ 415 -450 nm referentes as transições π -π * e pôlaron -π * , respectivamente, e uma terceira banda larga situada na faixa do visível entre ~ 700 à 850 nm indicando a transição π -pôlaron. 15,40,41,[44][45][46] Portanto, num catalisador compósito, o sinergismo entre a polianilina e o óxido metálico potencializa a oxidação de contaminantes sob radiação solar, aproveitando grande parte da energia incidente que corresponde à faixa do visível. A influência dessa propriedade na fotocatálise está associada às junções n-p formadas entre óxidos metálicos e polianilina, descritos como semicondutores tipo n e p, respectivamente.…”
Section: Polianilinaunclassified
“…In order to accelerate or improve their properties, inorganic-conductive polymer hybrids, which are nanoparticle-dispersed structures and/or conductive polymer-intercalated layered compounds, were examined as follows. Schnitzler, et al reported preparation of a TiO 2 nanoparticle/polyaniline hybrid [6]. Manganese oxide/polypyrrole nanocomposites were studied by Sharma et al [7].…”
Section: Open Accessmentioning
confidence: 99%